2020
DOI: 10.1186/s13765-020-00515-z
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals that Prx II gene knockout can down-regulate the allograft rejection of dermal mesenchymal stem cells

Abstract: In this study, we used RNA sequencing (RNA-seq) to analyze and compare bulk cell samples from wild-type (WT) dermal mesenchymal stem cells (DMSCs) (n = 3) and Prx II knockout DMSCs (n = 3). The purpose of the study was to elucidate the role of Prx II on allogeneic immune rejection of transplanted DMSCs. The results revealed differential expression of 472 genes (176 up-regulated and 296 down-regulated; p ≤ 0.05) between the PrxII +/+ (WT) and PrxII −/− sample groups. When highly regulated genes were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Therefore, we could not identify any embryos in our regression analysis with absolute zero reads of Rpl13a transcripts. This type of observation is not unprecedented and was reported by others 37 . Nonetheless, our Rpl13a ‐based regression analysis revealed widespread alterations in gene expression that could be mined as a resource via biological pathway analysis.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, we could not identify any embryos in our regression analysis with absolute zero reads of Rpl13a transcripts. This type of observation is not unprecedented and was reported by others 37 . Nonetheless, our Rpl13a ‐based regression analysis revealed widespread alterations in gene expression that could be mined as a resource via biological pathway analysis.…”
Section: Resultssupporting
confidence: 73%
“…This type of observation is not unprecedented and was reported by others. 37 Nonetheless, our Rpl13a-based regression analysis revealed widespread alterations in gene expression that could be mined as a resource via biological pathway F I G U R E 1 Embryos with the Rpl13a null allele arrest at the morula stage. (A) PCR genotyping of mouse preimplantation embryos to detect the Rpl13a KO allele.…”
Section: Morula Harboring the Homozygous Null Allele Of Rpl13a (Rpl13...mentioning
confidence: 99%
“…Preliminary laboratory studies have shown that Prx II-deficient DMSCs have a more pronounced effect on trauma treatment by increasing exosome secretion, which suggests the potential advantages of using Prx II -/-DMSCs to treat diseases. RNA sequencing results for Prx II +/+ DMSCs and Prx II -/-DMSCs have shown that Prx II -/-DMSCs are less immunogenic, which reduces the risks of stem cell therapy (19). In this study, we compared RNA sequencing results from Prx II +/+ DMSCs and Prx II -/-DMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The soft tissue on the surface of the mouse femur was carefully peeled off and the femur tissue was rinsed several times with a 1 mL syringe containing α-MEM culture solution, until it was transparent. Four rinsed femur cells were cultured in a medium containing BMSCs growth medium placed in a 95% air/5% CO2, 37° C incubator, and refreshed every three days [42][43][44].…”
Section: Acquisition Of Primary Mouse Bmscs and Hepatocytesmentioning
confidence: 99%